Rosette-Forming Glioneuronal Tumor of the Fourth Ventricle: A Case of Relapse Treated with Proton Beam Therapy - Antonella Cacchione; Angela Mastronuzzi; Andrea Carai; Giovanna Stefania Colafati; Francesca Diomedi-Camassei; Antonio Marrazzo; Alessia Carboni; Evelina Miele; Lucia Pedace; Marco Tartaglia; Maurizio Amichetti; Francesco Fellin; et al. (Diagnostics, 2021)
Rosette-forming glioneuronal tumors (RGNTs) are rare, grade I, central nervous system (CNS) tumors typically localized to the fourth ventricle. We describe a 9-year-old girl with dizziness and occipital headache. A magnetic resonance imaging (MRI) revealed a large hypodense posterior fossa mass lesion in relation to the vermis, with cystic component. Surgical resection of the tumor was performed. A RGNT diagnosis was made at the histopathological examination. During follow-up, the patient experienced a first relapse, which was again surgically removed. Eight months after, MRI documented a second recurrence at the local level. She was a candidate for the proton beam therapy (PBT) program. Three years after the end of PBT, the patient had no evidence of disease recurrence. This report underlines that, although RGNTs are commonly associated with an indolent course, they may have the potential for aggressive behavior, suggesting the need for treatment in addition to surgery. Controversy exists in the literature regarding effective management of RGNTs. Chemotherapy and radiation are used as adjuvant therapy, but their efficacy management has not been adequately described in the literature. This is the first case report published in which PBT was proposed for adjuvant therapy in place of chemotherapy in RGNT relapse.